High‐Performance Reversible Aqueous Zn‐Ion Battery Based on Porous MnOx Nanorods Coated by MOF‐Derived N‐Doped Carbon. Issue 26 (5th August 2018) - Fu, Yanqing; Wei, Qiliang; Zhang, Gaixia; Wang, Xiaomin; Zhang, Jihai; Hu, Yongfeng; Wang, Dongniu; Zuin, Lucia; Zhou, Tao; Wu, Yucheng; Sun, Shuhui
Abstract: Rechargeable aqueous zinc‐ion batteries (ZIBs) have been emerging as potential large‐scale energy storage devices due to their high energy density, low cost, high safety, and environmental friendliness. However, the commonly used cathode materials in ZIBs exhibit poor electrochemical performance, such as significant capacity fading during long‐term cycling and poor performance at high current rates, which significantly hinder the further development of ZIBs. Herein, a new and highly reversible Mn‐based cathode material with porous framework and N‐doping (MnO x @N‐C) is prepared through a metal–organic framework template strategy. Benefiting from the unique porous structure, conductive carbon network, and the synergetic effect of Zn 2+ and Mn 2+ in electrolyte, the MnO x @N‐C shows excellent cycling stability, good rate performance, and high reversibility for aqueous ZIBs. Specifically, it exhibits high capacity of 305 mAh g −1 after 600 cycles at 500 mA g −1 and maintains achievable capacity of 100 mAh g −1 at a quite high rate of 2000 mA g −1 with long‐term cycling of up to 1600 cycles, which are superior to most reported ZIB cathode materials. Furthermore, insight into the Zn‐storage mechanism in MnO x @N‐C is systematically studied and discussed via multiple analytical methods. This study opens new opportunities for designing low‐cost and high‐performance rechargeable aqueous ZIBs. Abstract : Based on a metal–organic framework, a unique porous Mn‐based cathode material with onion‐like N‐doped carbon and amorphous carbon shell is designed for high‐performance Zn‐ion batteries. Moreover, the electrode reaction mechanism is elucidated by combining electrochemical measurements and synchrotron X‐ray absorption spectroscopy. This work offers a new pathway for better understanding of a divalent metal‐ion insertion process.